Электроснабжение и электрооборудование угольных шахт за рубежом - Волощенко Н. И. Николай Иванович; Островский Э. П. Эдуард Пименович; Ихно В. А. Владимир Афанасьевич; Дикий Ю. А. (Москва, Недра, 1983)
Авт. указаны на обороте тит. л.